Isotopic Characterization of Water Masses in the Southeast Pacific Region: Paleoceanographic Implications - Reyes-Macaya, Dharma; Hoogakker, Babette; Martinez-Mendez, Gema; Llanillo, Pedro J.; Grasse, Patricia; Mohtadi, Mahyar; Mix, Alan; Leng, Melanie J.; Struck, Ulrich; McCorkle, Daniel C.; Troncoso, Macarena; Gayo, Eugenia M.; et al. (My University, 2022)
In this study, we used stable isotopes of oxygen (delta O-18), deuterium (delta D), and dissolved inorganic carbon (delta C-13(DIC)) in combination with temperature, salinity, oxygen, and nutrient concentrations to characterize the coastal (71 degrees-78 degrees W) and an oceanic (82 degrees-98 degrees W) water masses (SAAW-Subantarctic Surface Water; STW-Subtropical Water; ESSW-Equatorial Subsurface water; AAIW-Antarctic Intermediate Water; PDW-Pacific Deep Water) of the Southeast Pacific (SEP). The results show that delta O-18 and delta D can be used to differentiate between SAAW-STW, SAAW-ESSW, and ESSW-AAIW. delta C-13(DIC) signatures can be used to differentiate between STW-ESSW (oceanic section), SAAW-ESSW, ESSW-AAIW, and AAIW-PDW. Compared with the oceanic section, our new coastal section highlights differences in both the chemistry and geometry of water masses above 1,000 m. Previous paleoceanographic studies using marine sediments from the SEP continental margin used the present-day hydrological oceanic transect to compare against, as the coastal section was not sufficiently characterized. We suggest that our new results of the coastal section should be used for past characterizations of the SEP water masses that are usually based on continental margin sediment samples.
Keywords: oxygen and deuterium stable isotopes in seawater; carbon stable isotopes in dissolved inorganic carbon; southeast pacific; water mass distribution; paleoceanography proxies